In vitro characterization of cells derived from a patient with the GLA variant c.376A>G (p.S126G) highlights a non-pathogenic role in Fabry disease - Maximilian Breyer; Julia Grüner; Alexandra Klein; Laura Finke; Katharina Klug; Markus Sauer; Nurcan Üçeyler (Molecular Genetics and Metabolism Reports, 2024)
Fabry disease (FD) is a life-limiting disorder characterized by intracellular globotriaosylceramide (Gb3) accumulations. The underlying α-galactosidase A (α-GAL A) deficiency is caused by variants in the gene GLA. Variants of unknown significance (VUS) are frequently found in GLA and challenge clinical management. Here, we investigated a 49-year old man with cryptogenic lacunar cerebral stroke and the chance finding of the VUS S126G, who was sent to our center for diagnosis and initiation of a costly and life-long FD-specific treatment. We combined clinical examination with in vitro investigations of dermal fibroblasts (HDF), induced pluripotent stem cells (iPSC), and iPSC-derived sensory neurons. We analyzed α-GAL A activity in iPSC, Gb3 accumulation in all three cell types, and action potential firing in sensory neurons. Neurological examination and small nerve fiber assessment was normal except for reduced distal skin innervation. S126G iPSC showed normal α-GAL A activity compared to controls and no Gb3 deposits were found in all three cell types. Baseline electrophysiological characteristics of S126G neurons showed no difference compared to healthy controls as investigated by patch-clamp recordings. We pioneer multi-level cellular characterization of the VUS S126G using three cell types derived from a patient and provide further evidence for the benign nature of S126G in GLA, which is of great importance in the management of such cases in clinical practice.